ANALYSIS OF THE INFLUENCE OF RELIGIOSITY, ENVIRONMENT, AND REPUTATION FACTORS ON CUSTOMER DECISIONS ON SAVING AT KSPPS BMT AMANAH UMMAH - Iin Emy Prastiwi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to determine: religious factors, profit sharing factors, environmental factors, reputation factors, location factors have a partial and simultaneous influence on customer decisions to save at KSPPS BMT Amanah Ummah. This study uses a quantitative approach. The sample in this study were 100 Amanah Ummah KSPPS BMT customers. Data collection methods used were questionnaires and documentation. conducted include validation and reliability testing. Hypothesis testing uses multiple regression analysis. The results of research on the factors that influence the decision to save at KSPPS BMT Amanah Ummah show that religious, the environment and reputation have positive significantly influence the decision to save at KSPPS BMT Amanah Ummah.